O Levante dos tenentes como fenômeno jornalístico: a narrativa do Correio da Manhã - Andrade, Geovani Anicio (2018)
This paper analyzes the performance of the newspaper Correio da Manhã as one of the important elements of the crisis of the 1920s in the First Republic. In addition, we seek to present how the journal constructed a narrative about the rebel movement of young officers and squares of the Brazilian army, known in the historiography as tenentismo. This political project of the newspaper went on to construct the figure of one of the main tenentistas leaders, Luiz Carlos Prestes, as a national hero until the moment of his conversion to communism.